Writing Tricksters : Mythic Gambols in American Ethnic Fiction. - Smith, Jeanne Rosier (University of California Press, 2022)
Writing Tricksters examines the remarkable resurgence of tricksters--ubiquitous shape-shifters who dwell on borders, at crossroads, and between worlds--on the contemporary cultural and literary scene. Depicting a chaotic, multilingual world of colliding and overlapping cultures, many of America's most successful and important women writers are writing tricksters. Taking up works by Maxine Hong Kingston, Louise Erdrich, and Toni Morrison, Jeanne Rosier S.
Keywords: Kingston, Maxine Hong -- Criticism and interpretation.; Erdrich, Louise -- Criticism and interpretation.; Morrison, Toni -- Criticism and interpretation.; Erdrich, Louise; Kingston, Maxine Hong; Morrison, Toni; American fiction -- Women authors -- History and criticism.; Tricksters in literature.; American prose literature -- Minority authors -- History and criticism.; American prose literature -- 20th century -- History and criticism.; Literature and folklore -- United States -- History -- 20th century.; Women and literature -- United States -- History -- 20th century.; Minority women in literature.; Ethnic groups in literature.; Ethnicity in literature.; Narration (Rhetoric); American literature -- Women authors -- History and criticism.; American fiction -- 20th century -- History and criticism.; Tricksters dans la littérature.; Prose américaine -- Auteurs issus des minorités -- Histoire et critique.; Prose américaine -- 20e siècle -- Histoire et critique.; Littérature et folklore -- États-Unis -- Histoire -- 20e siècle.; Femmes et littérature -- États-Unis -- Histoire -- 20e siècle.; Femmes issues des minorités dans la littérature.; Groupes ethniques dans la littérature.; Ethnicité dans la littérature.; Narration.; Écrits de femmes américains -- Histoire et critique.; Roman américain -- 20e siècle -- Histoire et critique.; LITERARY CRITICISM / American / General; American fiction; American fiction -- Women authors; American literature -- Women authors; American prose literature; American prose literature -- Minority authors; Ethnic groups in literature; Ethnicity in literature; Literature and folklore; Minority women in literature; Tricksters in literature; Women and literature; United States; 1900-1999; Criticism, interpretation, etc.; History